2019
DOI: 10.1002/lio2.284
|View full text |Cite
|
Sign up to set email alerts
|

Office‐based corticosteroid injections as adjuvant therapy for subglottic stenosis

Abstract: Objective Subglottic stenosis (SGS) is a serious, potentially life‐threatening disorder that is difficult to treat due to significant recurrence rates. While conventional treatment of SGS relies heavily on serial endoscopic dilation procedures, this study aims to characterize the efficacy of incorporating subglottic corticosteroid injections in increasing surgery‐free intervals (SFIs) for a cohort of patients at a university‐based medical system. Study Design Retrospective chart review. Methods All SGS patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
31
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(39 citation statements)
references
References 15 publications
4
31
0
4
Order By: Relevance
“…1). Pan and Rosow examined a retrospective cohort of SGS patients of various etiologies who underwent a mean of 4.2 injections following ED and demonstrated a significantly increased SFI following SILSI [85]. A study of 24 SGS patients of various etiologies who underwent a mean of 4.08 injections (88% had undergone ED prior to SILSI) showed that 71% of patients did not require further surgery after SILSI.…”
Section: Adjuvant Therapymentioning
confidence: 99%
“…1). Pan and Rosow examined a retrospective cohort of SGS patients of various etiologies who underwent a mean of 4.2 injections following ED and demonstrated a significantly increased SFI following SILSI [85]. A study of 24 SGS patients of various etiologies who underwent a mean of 4.08 injections (88% had undergone ED prior to SILSI) showed that 71% of patients did not require further surgery after SILSI.…”
Section: Adjuvant Therapymentioning
confidence: 99%
“…[4][5][6][7] Treatment modalities have evolved over time from open surgical procedures to endoscopic dilations, laser surgery, and adjuvant intralesional steroid injections. [8][9][10][11][12] Generally, treatments are tailored to severity and recurrence of a patient's breathing, and possibly voice, dysfunction.…”
Section: Introductionmentioning
confidence: 99%
“…Small retrospective studies have shown up to an 8- to 12-month increase in surgery-free interval (SFI). 12 , 13 This coincides with stable or even improved airway patency with SILSIs. 14 , 15 Patients indicate less dyspnea, decreased vocal handicap, and improved voice-related quality of life.…”
mentioning
confidence: 54%
“…While there are several reports in the literature describing outcomes with SILSIs, extant literature is lacking regarding clinically identified systemic side effects. [12][13][14][15][16][17][18][19] Hoffman et al noted a similar rate of adverse effects (31%) but a different set of side effects incident to the injection procedure itself, including transient airway restriction, cough, nasal pain, and a single instance of possible hypercortisolism (weight gain, headaches, insomnia, restlessness). 16 Multiple patients in the present study indicated discomfort with injection or a vasovagal response, but these were not included in our analysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation